Protection of the Right to Freedom of Assembly under Ethiopian Law: Gaps and the Way Forward - Gelaye, Tsega Andualem (Mizan law review, 2017)
The right to Freedom of assembly is among the political rights enshrined under the Constitution of the Federal Democratic Republic of Ethiopia (FDRE). Despite the frequent reporting of its rampant violation by human right monitoring bodies and the media, one cannot find a research that assesses the adequacy of protection offered to the right by the Ethiopian Constitution and other laws of the country. This article seeks to fill this gap by indicating some of the key problems with the existing legal regime governing the right and the prevailing practice. As such, it argues that the present Constitution of Ethiopia gives an incomplete protection to the right, by failing to go beyond listing grounds of limiting it without incorporating additional guarantees of preventing arbitrary restrictions such as necessity and proportionality in explicit manner. Moreover, it contends that this problem was exacerbated by the presence of too many loopholes in the Peaceful Demonstration and Public Political Meetings Proclamation that ranges from inadequate rules governing notification procedure to the absence of fair hearing and judicial or administrative review procedures in the law. Suggestions to improve the legal guarantees for freedom of assembly in Ethiopia are also made in the article in light of lessons from the experience of other national and international jurisdictions with better standards of protection. Furthermore, it asserts that reforming the legal regime applicable to freedom of assembly and ensuring its appropriate implementation requires a strong political will of the ruling party in promoting good governance, respecting rule of law and strengthening democratic institutions.